East Meets West: Toward a Universal Ethic of Virtue for Global Business - Koehn, Daryl 1955- (2013)
Rudyard Kipling famously penned, “East is East, West is West, and never the twain shall meet.” His poetic line suggests that Eastern and Western cultures are irreconcilably different and that their members engage in fundamentally incommensurable ethical practices. This paper argues that differing cultures do not necessarily operate by incommensurable moral principles. On the contrary, if we adopt a virtue ethics perspective, we discover that East and West are always meeting because their virtues share a natural basis and structure. This article sketches the rudiments of what a universal virtue ethic might look like. Such an ethic is especially relevant and valuable in this era of global business.
Keywords: Global business; Virtue Ethics; universal ethic; Ethical Relativism; Confucius; Aristotle